Parents' Contribution in Student Program Management at SMP N 1 Tirtomoyo - Istanto, Istanto; Sukirman, Sukirman; Zuhaery, Muhammad (FKIP - Universitas Riau, 2025)
This study aims to examine the extent of parental contribution to student affairs programs at SMP Negeri 1 Tirtomoyo. This research employs a qualitative approach with a descriptive method to comprehensively illustrate the level of parental contribution in student affairs management. Data were collected through interviews with the school principal, vice principal in charge of student affairs, homeroom teachers, and representatives of students' parents, along with observations of student affairs activities and document analysis. Data analysis techniques include data reduction, data presentation, and verification to derive accurate conclusions. The validity of the data was ensured through source and technical triangulation. The findings indicate that parental contribution covers five main aspects: 1) Enhancing students' knowledge and motivation, 2) Developing human resources, 3) Increasing social awareness, 4) Encouraging students' interests and talents, and 5) Supporting students' achievements. Parents actively participate in motivating their children, supporting extracurricular activities, and contributing to school funding and promotion through social media. The high level of parental contribution positively affects students' academic performance and the school's reputation, ultimately leading to an increase in student enrollment during the PPDB (new student admission process).